Method for Measuring the Three-Dimensional Morphology of Near-Wall Bubbles and Droplets Based on LED Digital Holography - Wang, Jinqing (Langmuir : the ACS journal of surfaces and colloids, 2024)
Digital holography, recognized for its noncontact nature and high precision in three-dimensional imaging, is effectively employed to measure the morphology of bubbles and droplets. However, in terms of near-wall bubbles and droplets, such as confined bubbles in microfluidic chips, the measurement of the interface morphology of bubbles near the glass surface has not yet been resolved due to the coherent noise resulting from glass surface reflections in microfluidic chips. Accordingly, an off-axis digital holography system was devised by using Linnik interferometry. Measuring the confined bubble interface near the wall within a microfluidic chip and droplet evaporation on solid surfaces was studied. Partially coherent LED sources and reference light modulation techniques were employed in the optical setup to mitigate the coherent noise. Dual exposure and weighted least-squares unwrapping algorithms were introduced to correct phase distortions, enhancing image quality. Imaging two confined CO2 bubbles was done near the wall in silicon oil within a porous microfluidic chip, and contact angles of 4.7 and 4.5° were measured. Additionally, the measurement of the three-dimensional morphology of vertically evaporating deionized water droplets on a glass surface was done, due to which calculation of contact angles at various orientations was possible. This work offers a feasible new method for measuring the 3D interface morphology of bubbles and droplets, particularly in microfluidic visualization, addressing current measurement gaps